2020
DOI: 10.1037/cbs0000169
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported depressive symptoms in active and retired professional hockey players.

Abstract: This study presents data on self-reported depressive symptoms in active and retired professional hockey players and examines psychosocial factors related to depressive symptoms. Data were derived from an online survey that was sent to 1,276 active players and approximately 4,000 retired players in the Professional Hockey Players’ Association (PHPA). A total of 409 participants completed the survey, representing 56% of those who opened the survey link. In our sample, retired players reported moderate to very se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Results appeared different, depending on samples and conditions. In the study by Aston et al [ 30 ], for retired and active hockey players, greater alexithymia was associated with greater depressive symptoms. Medina-Porqueres et al [ 31 ] showed that seniors who are physically active have lower results in alexithymia and depression scores than those who are not physically active.…”
Section: Resultsmentioning
confidence: 99%
“…Results appeared different, depending on samples and conditions. In the study by Aston et al [ 30 ], for retired and active hockey players, greater alexithymia was associated with greater depressive symptoms. Medina-Porqueres et al [ 31 ] showed that seniors who are physically active have lower results in alexithymia and depression scores than those who are not physically active.…”
Section: Resultsmentioning
confidence: 99%
“…Here, our results are in line with those of Aston et al, regarding both retired and active hockey players. In fact, more pronounced alexithymia was associated with greater depressive symptoms [ 29 ]. We know now that depression acts as a strong moderator between alexithymic features and psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…A range of problematic psychological outcomes often accompany athletic career cessation, these include emotional distress, depression, feelings of loss and isolation, diminished subjective well-being and identity disruption (Aston et al 2020). More recently, these outcomes have been tied to formative sports contexts (Stambulova et al 2020), and sports psychology researchers have suggested that retirement from sport is less problematic when it is planned as a process (with the support of others), rather than if it occurs as a sudden event, for example, as a result of injury or de-selection (Esopenko et al 2020;Lally 2007;Park et al 2013), as well as in scenarios where athletes align with a purpose-based identity rather than a performance-based identity-that is, an identity that is more vulnerable to contingency-based self-esteem issues (Houltberg et al 2018).…”
Section: Sports Retirement Researchmentioning
confidence: 99%